Hydroxychloroquine with azithromycin in patients hospitalized for mild and moderate COVID-19 - Elisa Baranski Lamback; Monica Amorim de Oliveira; Andrea Ferreira Haddad; André Filipe Marcondes Vieira; Armando Leão Ferreira Neto; Taciana da Silva Maia; Juliana de Rezende Chrisman; Pedro Pimenta de Mello Spineti; Marco Antonio de Mattos; Eduardo Costa (Brazilian Journal of Infectious Diseases, 2021)
Objectives: To assess the efficacy of hydroxychloroquine in combination with azithromycin in terms of clinical and biochemical outcomes in adult patients with COVID-19 hospitalized for acute respiratory distress syndrome (ARDS), and to describe the occurrence of adverse events. Method: Retrospective comparative study, based in a quaternary private hospital in Rio de Janeiro, Brazil, involving 193 adult patients hospitalized for mild and moderate COVID-19 related ARSD, analyzing treatment efficacy based on clinical and biochemical outcomes. Results: The active group comprised 101 (52.3%) patients using hydroxychloroquine associated with azithromycin and the control group 92 (47.7%) patients who did not take these medications. Median age was 59 (47–70) in the active group and 65 (47−77) in the control group (p < 0.05). Patients in the control group had greater extent of pulmonary involvement on baseline chest CT scans (p < 0.05). All other baseline variables (BMI, comorbidities, previous use of medications and biochemical assessments) were similar between groups. In the medication group, 25% (25 out of 101) were admitted to the ICU, compared to 21% (19 out of 92) in the control group (p > 0.05). No difference in mortality, duration of non-invasive oxygen use or duration of hospitalization was seen between groups. The therapeutic regimen was well tolerated, with only eight (7.9%) patients presenting gastrointestinal symptoms and eight (7.9%) patients withdrawn treatment due to QTc prolongation. Conclusions: Patients treated with hydroxychloroquine combined with azithromycin and the control group had similar clinical outcomes. This therapeutic regimen was considered ineffective in hospitalized patients with mild to moderate COVID-19 related ARDS and was associated with few non-severe adverse events.